Uporaba funkcionalne električne stimulacije pri kolesarjenju oseb po poškodbi hrbtenjače - Kočar, Barbara (Rehabilitacija (Ljubljana), 2015)
Cycling with FES has been used in rehabilitation for over 30 years. Its purpose is to stimulate large muscle groups of the paralysed lower limbs to create a cyclic movement of the legs. In FES-cycling the quadriceps, hamstrings and gluteus maximus are stimulated with surface electrodes through a computer. Many studies report on the physiological adjustments after cycling with FES in individuals after spinal cord injury, stroke and cerebral palsy. Many studies have reported beneficial effects of FES cycling, such as increasing muscle mass, better blood flow, reduction of pressure ulcers, improved self-image and reduction of bone mineral density loss.
Keywords: cycling; functional electrical stimulation; funkcionalna električna stimulacija; hrbtenjača; injuries; kolesarjenje; okvara; pregled literature; Review Literature as Topic; review of literature; Spinal Cord; spinal cord impairment